516. SARS-CoV-2 Exhibits Clade-specific Differences in Nasopharyngeal Viral Loads. (31st December 2020) - Nam, Hannah; Lorenzo-Redondo, Ramon; Roberts, Scott C; Simons, Lacy; Achenbach, Chad; Hauser, Alan R; Ison, Michael G; Hultquist, Judd F; Ozer, Egon A
Abstract: Background: The rapid spread of SARS-CoV-2, the causative agent of Coronavirus disease 2019 (COVID-19), has been accompanied by the emergence of distinct viral clades, although their clinical significance has yet to be fully elucidated. While whole genome sequencing efforts have identified viral diversity over time, less is known about the clinical significance of this diversity. This study assessed the nasopharyngeal viral loads within patients over time to determine if these changes affect clinical parameters. Methods: Samples were collected from patients presenting to Northwestern Memorial Hospital in Chicago, IL with a positive SARS-CoV-2 RT-PCR from nasopharyngeal swabs. Cycle threshold (Ct) values less than 35 were considered positive, and whole genome sequencing was performed by reverse transcription, multiplex PCR, and Nanopore sequencing. Phylogenetic analysis was conducted on sequenced isolates and compared with publicly available global sequences. Sequence characteristics and viral loads were correlated with each clade. Results: 177 samples were analyzed from March 14, 2020, through May 1, 2020. Most of the sequences (92.6%) clustered in three main clades [Figure 1]. Clade IDs were ordered by relative abundance as Clades 1 (n=122, 68.9%), 2 (n=34, 19.2%), and 3 (n=8, 4.5%). Over this time, Clade 1 viruses have been increasing in incidence across the USA and globally while Clade 2 viruses were uniquely predominant in Illinois with limited global distribution. Ct values were compared across clades [Figure 2]. Significantly lower average Ct values (higher viral loads) were observed in Clade 1 relative to both Clade 2 (p=0.0002) and Clade 3 (p=0.0011). These findings were independent of time from symptom onset to specimen collection. Phylogenetic Analysis of SARS-CoV-2 Isolates with Number of Clades and Clade Distribution Associations Between Viral Clade and Ct Value Conclusion: These data suggest that SARS-CoV-2 genotype may impact viral load in the upper airways. It remains to be determined whether this difference in clades may impact transmission potential and overall viral spread. Further longitudinal studies with more specimens and associated clinical data are needed. Disclosures: Michael G. Ison, MD MS, AlloVir (Consultant)